2019
DOI: 10.1097/aog.0000000000003415
|View full text |Cite
|
Sign up to set email alerts
|

Association of Labor With Neonatal Respiratory Outcomes at 36–40 Weeks of Gestation

Abstract: OBJECTIVE: To evaluate whether labor is associated with lower odds of respiratory morbidity among neonates born from 36 to 40 weeks of gestation and to assess whether this association varies by gestational age and maternal diabetic status. METHODS: We conducted a secondary analysis of women in the Assessment of Perinatal Excellence obstetric cohort who delivered across 25 U.S. hospitals over a 3-year period. Women with a singleton liveborn non-anomalous neonate who delivered from 36 to 40 weeks of gestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Furthermore, they found similar findings within their diabetic cohort which, unlike our study, included both pregestational and gestational diabetics. 23 The findings of our study also have several research implications. First, further research is needed to determine whether, among pregnancies complicated by GDM, the difference in neonatal respiratory morbidity is solely a function of labor or also a function of mode of delivery.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, they found similar findings within their diabetic cohort which, unlike our study, included both pregestational and gestational diabetics. 23 The findings of our study also have several research implications. First, further research is needed to determine whether, among pregnancies complicated by GDM, the difference in neonatal respiratory morbidity is solely a function of labor or also a function of mode of delivery.…”
Section: Discussionmentioning
confidence: 64%
“…Second, it has been suggested that the protective effect of labor on neonatal respiratory outcomes can differ by gestational age. 23 Further research should be conducted to determine whether this is also seen in pregnancies complicated by GDM.…”
Section: Discussionmentioning
confidence: 99%
“…[35] The higher incidence of cesarean deliveries in LGA infants likely also increases the risk of respiratory complications in the newborn. [36] In addition, meconium aspiration may be more common in LGA infants. [4] LGA birth weight and shoulder dystocia Larger infants, especially with macrosomia, are at increased risk for shoulder dystocia, brachial plexus injury and clavicular fracture, [4 37 38] and the risk of birth injury increases with the severity of macrosomia.…”
Section: Lga Birth Weight and Neonatal Intensive Care Admissionmentioning
confidence: 99%